Two genera of Braconinae (Hymenoptera, Braconidae) in China, with descriptions of four new species - Wang, Yi-Ping (Pensoft Publishers, 2010)
Abstract. Two genera, namely Dolabraulax Quicke and Scutibracon Quicke of Braconinae (Hymenoptera: Braconidae) from China are studied for the first time, and four new species, namely Dolabraulax jigongshanus Wang & Chen, sp. n., Dolabraulax flavus Wang & Chen, sp. n., Dolabraulax brevivena Wang & Chen, sp. n. and Scutibracon fujianensis Wang & Chen, sp. n. are fully described and illustrated. The examined specimens are deposited in the Parasitic Hymenoptera Collection, Zhejiang University, Hangzhou, China (ZJUH).